Hydrothermal Alteration of High Sulfidation Epithermal Deposits in Secang Area, Tulungagung, East Java, Indonesia - Anastasia Dewi Titisari; Septyo Uji Pratomo; Arifudin Idrus (Geological Engineering Department Universitas Gadjah Mada, 2021)
This research aims to determine geological condition and alteration in an epithermal high sulfidation mineralization as an initial guide for further exploration stages. Detailed geological mapping with scale of 1:12,500 is conducted to identify geological aspects and distribution of alteration zones. Selected rocks samples were prepared for laboratory analysis which are petrography, XRD (X-Ray Diffraction), and FA-AAS (Fire Assay-Atomic Absorption Spectrometry) analyse. Geological condition of the study area consists of six rock units including andesite lava, andesite breccia, diorite intrusion, polymict breccia, limestone, and alluvial deposit. Geological structures found are left strike-slip fault with right strike-slip fault as accompany. Result of XRD analysis shows the presence of clay minerals group: smectite, kaolinite, illite, diaspore, alunite, and pyrophillite. The alteration zones of study area are propylitic, argillic, advance argillic, and silisification zones. The further exploration stage is recommended to focus at the southwest and northeast of study area.